Does public capital expenditure reduce energy poverty? Evidence from Nigeria - Stephen Kelechi Dimnwobi; Favour Chidinma Onuoha; Benedict I. Uzoechina; Chukwunonso Ekesiobi; Ebele Stella Nwokoye (African Governance and Development Institute (AGDI), 2022)
Purpose - Given the ever-growing fiscal commitments of Nigeria and her chequered history of electricity generation and distribution, the fortunes of the energy sector in the country have been affected by the prevalence of energy poverty. Government policies such as public capital expenditure (PCE) present a crucial option for reducing energy poverty in Nigeria, providing the research impetus for this study. Design/methodology/approach -To investigate the relationship between government capital spending and five distinct energy poverty proxies, this research applies the Bayer-Hanck cointegration system and the Auto-Regressive Distributed Lag (ARDL) bound test. Findings -The findings indicate that public capital spending in Nigeria worsens energy poverty by reducing access to electricity, urban electrification, renewable energy consumption, and renewable electricity generation, with a positive but insignificant influence on rural electrification. Originality/value - This inquiry presents a pioneering investigation of the nexus between PCE and energy poverty in Nigeria. Also, aside from the variables of energy poverty adopted by existing studies, this study incorporates renewable energy consumption and renewable electricity output with implications for energy poverty and sustainable development.
Keywords: 330; Public Capital Expenditure; Energy Poverty; Electricity; Nigeria